Be Careful What You Wish For - Archer, Jeffrey 1940-; Jennings, Alex; Wilson, Laura; Leow, Jenny; Macmillan Audio (Firm) (New York : Macmillan Audio, 2014)
Follow the struggles and triumphs of the Clifton and Barrington families into the 1960's: the construction of a luxury ocean liner which comes under sabotage from the IRA; the Clifton family's entry into the London art scene; and a sweeping ending with all of the Barringtons and the Cliftons aboard the ship for its maiden voyage.
Keywords: Families -- Fiction -- History -- 20th century -- England; Social classes -- Fiction -- England; Audiobooks; Audiobooks; Domestic fiction